Peculiarities of platelet hemostasis changes in patients with arterial hypertension and coronary artery disease, depending on the presence of microalbuminuria - Anna I. Pastushyna (Kazimierz Wielki University, 2016)
Pastushyna Anna I. Peculiarities of platelet hemostasis changes in patients with arterial hypertension and coronary artery disease, depending on the presence of microalbuminuria. Journal of Education, Health and Sport. 2016;6(9):610-615. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.158164 http://ojs.ukw.edu.pl/index.php/johs/article/view/3887         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Peculiarities of platelet hemostasis changes in patients with arterial hypertension and coronary artery disease, depending on the presence of microalbuminuria   Anna I. Pastushyna   Bogomolets national medical university, Department of propedeutics of internal medicine N1 Abstract The activity of platelets and microalbuminuria can be considered as a reflection of endothelial function both in arterial hypertension and in other cardiovascular diseases. To assess the platelet hemostasis we examined 98 people: 14 apparently healthy (Group 1, control), 34 patients with arterial hypertension, the 2-nd stage, in combination with coronary artery disease with concomitant MAU (group 2), 50 patients with arterial hypertension, the 2-nd stage, in combination with coronary artery disease without concomitant MAU (3 Group). Analysis of induced platelet aggregation revealed decrease in ADP and AA-induced aggregation in the study groups of patients, which may be due to the treatment of this category of patients with acetylsalicylic acid, which has a direct effect on the AA-stimulated aggregation. Decrease of expression of ADP aggregation in patients of surveyed groups may be due to a receiving clopidogrel by patients. It is noteworthy that despite treatment with antiplatelet drugs, collagen and epinephrine-induced aggregation were not significantly different from the control group.   Key words: arterial hypertension, coronary artery disease, microalbuminuria, hemostasis, platelets aggregation.